Intelligent sensor networks : the integration of sensor networks, signal processing, and machine learning - Hu, Fei, 1972-; Hao, Qi, 1973- (Boca Raton, FL : Taylor & Francis, 2013)
'In the last decade, wireless or wired sensor networks have attracted much attention. However, most designs target general sensor network issues including protocol stack (routing, MAC, etc.) and security issues. This book focuses on the close integration of sensing, networking, and smart signal processing via machine learning. Based on their world-class research, the authors present the fundamentals of intelligent sensor networks. They cover sensing and sampling, distributed signal processing, and intelligent signal learning. In addition, they present cutting-edge research results from leading experts'--
Includes bibliographical references and index.
Keywords: Wireless sensor networks